MODELING TEACHER PERFORMANCE OPTIMIZATION: INTEGRATING TECHNOLOGY, KNOWLEDGE MANAGEMENT, AND LOCAL WISDOM IN VOCATIONAL EDUCATION - Nunung Siti Nurbayani; Soewarto Hardhienata; Dian Wulandari (SUJANA: Education and Learning Review, 2025)
This study examines an integrative model of teacher performance in Vocational High Schools designated as Centers of Excellence in Banten Province, Indonesia, by analyzing the roles of leadership, religiosity, empowerment, knowledge management, local wisdom (Sabilulungan), and information technology utilization. Using a mixed-methods sequential exploratory design, the research combines qualitative exploration with quantitative analysis through Partial Least Squares–Structural Equation Modeling (PLS-SEM) and the Scientific Identification Theory for Operational Research in Education Management (SITOREM). Data were collected from 254 civil servant teachers across 28 vocational schools using structured questionnaires. The findings indicate that information technology utilization has the strongest direct effect on teacher performance, followed by knowledge management, Sabilulungan, and empowerment. In contrast, Banten local leadership and religiosity do not show significant direct effects. Mediation analysis reveals that information technology utilization significantly strengthens the influence of empowerment and knowledge management on teacher performance, whereas Sabilulungan does not function as a significant mediator. The study contributes to the literature by proposing an optimization-oriented performance model that integrates technological capability with cultural and managerial dimensions, offering practical implications for improving teacher performance in vocational education.